Estimate of production of gaseous nitrogen in the human body based on 15N analysis of breath N2 after administration of [15N2]urea: Dedicated to Professor Dr habil. Hans Faust on the occasion of his 85th birthday. [electronic resource] - Junghans, Peter (Isotopes in environmental and health studies, 2013)
After oral administration of [ ¹⁵N ₂]urea (1.5 mmol, 95 atom% ¹⁵N), we found that breath N ₂ was significantly ¹⁵N-labelled. The result suggests that molecular nitrogen in breath must be partly produced endogenously. Based on a metabolic model, the endogenous N ₂ production was estimated to be 0.40±0.25 mmol kg ⁻¹ d ⁻¹ or 2.9±1.8 % of the total (urinary and faecal) N excretion in fasted healthy subjects (n =4). In patients infected with Helicobacter pylori (n =5), the endogenous N ₂ production was increased to 1.24±0.59 mmol kg ⁻¹ d ⁻¹ or 9.0±4.3 % of the total N excretion compared to the healthy controls (p <0.05). We conclude that N balance and gas exchange measurements may be affected by endogenously produced nitrogen, especially in metabolic situations with elevated nitrosation, for instance in oxidative and nitrosative stress-related diseases such as H. pylori infections.